Knowledge, attitudes, and practices of family caregivers for patients with cerebral infarction toward home-based care - Chen, Zhipeng; Zhou, Xiaohua; Jiang, Lu; Song, Chunmei; Wang, Shufang; Zhao, Huilan; Liu, Jianping; Ma, Xiangxiang; Yu, Jia (Frontiers in Public Health, 2024)
Objective: This study aimed to assess the knowledge, attitudes, and practices (KAP) among family caregivers of patients with cerebral infarction toward home-based care. Methods: This web-based cross-sectional study was conducted between October 2023 to February 2024 at Yancheng Third People's Hospital. A self-designed questionnaire was developed to collect demographic information, and assess the KAP among family caregivers of patients with cerebral infarction towards home-based care. Results: A total of 761 questionnaires were included in the study. Among the participants, 453 (59.53%) were female, and 548 (72.01%) lived with the patients. The mean knowledge, attitudes and practices scores were 6.67±1.73 (possible range: 0-9), 32.95±2.46 (possible range: 9-45), and 28.64±4.39 (possible range: 8-40), respectively. Path analysis showed the direct effect of knowledge on both attitudes (β = 0.885, p < 0.001) and practices (β = 1.295, p < 0.001), as well as of attitudes on practices (β = 0.838, p < 0.001). Conclusion: Family caregivers of patients with cerebral infarction have sufficient knowledge, positive attitudes and proactive practices toward home-based care. However, they still exhibit deficiencies in certain aspects of knowledge, attitudes, and practice. Developing personalized educational strategies may be instrumental in enhancing family caregivers' knowledge of home-based care. This, in turn, could improve their attitudes and elevate their practice levels.